Pemberdayaan Kelompok Wanita Tani di Desa Bonto Karaeng Melalui Pelatihan Pembuatan Pupuk Organik Cair dari Limbah Rumah Tangga - Jumarni Jumarni; Andi Cakra Yusuf; Hafizhah Al-Amanah (I-Com: Indonesian Community Journal, 2024)
There are various types of household waste, one of which is organic waste such as rice washing water and banana peels, which have great potential to be recycled into liquid organic fertilizer. This community service activity aims to empower the Women Farmers Group in Bonto Karaeng Village, Sinoa Subdistrict, Bantaeng Regency through training on making liquid organic fertilizer from household waste, which was held on August 30, 2024, at the PKK Secretariat. The activity was carried out in three stages, namely counseling, training, and evaluation using the Participatory Rural Appraisal (PRA) method. The training results showed that the participants had a good understanding of the material presented and were able to apply it directly in making liquid organic fertilizer. This is reinforced by the results of the questionnaire which shows an average increase in knowledge of 80%. The participants hope that this activity can equip them with the skills to process household waste into liquid organic fertilizer in order to reduce environmental impact and increase agricultural productivity